2016
DOI: 10.1007/s00423-016-1500-6
|View full text |Cite
|
Sign up to set email alerts
|

Chylous ascites after colorectal cancer surgery: risk factors and impact on short-term and long-term outcomes

Abstract: A major drawback of this study was that the definition of chylous ascites was solely based on clinical signs. Nevertheless, we can conclude that chylous ascites after colorectal cancer surgery is associated with a shorter operative time and the number of retrieved lymph nodes, but is not associated with the short-term and long-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 21 publications
5
26
0
Order By: Relevance
“…D3 extended mesenterectomy entails the removal of all fatty tissue from the predefined D3 area [ 2 ], made possible and safe through preoperative 3D multi-detector computed tomography (MDCT) vascular anatomy reconstruction [ 3 , 4 ]. Literature suggests that the incidence of chylous ascites after surgery, i.e., urological, gynecological, vascular, and liver (non-intestinal lymph), is estimated to be between 0.17 and 7.0% [ 5 ], while the incidence rates may be higher after gastric, colorectal, pancreatic, and small bowel surgery (intestinal lymph) with a rate between 1.0 and 11.8% [ 1 , 5 , 6 ]. Reports on the incidence rates of chylous ascites after D3 extended mesenterectomy are scarce in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…D3 extended mesenterectomy entails the removal of all fatty tissue from the predefined D3 area [ 2 ], made possible and safe through preoperative 3D multi-detector computed tomography (MDCT) vascular anatomy reconstruction [ 3 , 4 ]. Literature suggests that the incidence of chylous ascites after surgery, i.e., urological, gynecological, vascular, and liver (non-intestinal lymph), is estimated to be between 0.17 and 7.0% [ 5 ], while the incidence rates may be higher after gastric, colorectal, pancreatic, and small bowel surgery (intestinal lymph) with a rate between 1.0 and 11.8% [ 1 , 5 , 6 ]. Reports on the incidence rates of chylous ascites after D3 extended mesenterectomy are scarce in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Previous data showed that chylous ascites in patients after colorectal surgery didnot affect their survival [7]. However, a limited report of a small sample size showed a higher rate of cancer recurrence in patients with chylous ascites.…”
Section: Discussionmentioning
confidence: 91%
“…Postoperative chylous ascites is caused by direct surgical trauma to the major lymphatic tributaries. Recent studies showed that long-term outcomes were not affected by the presence of chylous ascites [7]. However, chylous ascites is known to prolong hospital stays by necessitating treatment with total parenteral nutrition or a medium-chain triglyceride diet [5].…”
Section: Introductionmentioning
confidence: 99%
“…11 articles reported the dissecting equipment used including ultrasonic coagulating shears, electrothermal bipolar vessel sealers and/or electrosurgery[ 1 , 2 , 10 , 13 , 17 , 22 , 24 , 25 , 27 , 28 , 34 ] (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…There was no uniformity in the definition of CL/CA in four studies that defined it[ 1 , 2 , 13 , 17 ]. Most commonly, diagnosis was based on the appearance of typical non-infected, white milky fluid from surgical drains.…”
Section: Resultsmentioning
confidence: 99%